Positive electrode active material for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery

By using nickel-manganese composite hydroxide as a precursor, a lithium-nickel-manganese composite oxide positive electrode active material with high capacity and high energy density is prepared, which solves the problems of high cost and insufficient performance of lithium-ion secondary batteries, and achieves good battery performance under high temperature conditions.

CN114804226BActive Publication Date: 2025-03-04SUMITOMO METAL MINING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202210342965.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2016-10-31
Filing Date
2017-10-31
Publication Date
2025-03-04
Estimated Expiration
2037-10-31

AI Technical Summary

Technical Problem

The positive electrode active substances of existing lithium-ion secondary batteries are costly and difficult to meet the needs of high capacity and high energy density, especially the problems of severe self-discharge and reduced charge and discharge life under high temperature conditions.

Method used

Using nickel-manganese composite hydroxide as the precursor, a lithium nickel-manganese composite oxide positive electrode active material with high capacity and high energy density was prepared through specific crystallization steps and calcination conditions, and gelation was suppressed by adjusting the thickness and composition of the manganese enrichment layer.

Benefits of technology

The high capacity and high energy density of non-aqueous electrolyte secondary batteries are achieved, the production cost of lithium-ion secondary batteries is reduced, and the good self-discharge performance and charge and discharge life are maintained under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114804226B_ABST
    Figure CN114804226B_ABST
Patent Text Reader

Abstract

The present invention provides: a positive electrode active material having high capacity and high energy density and capable of reducing the amount of eluted lithium when used in a non-aqueous electrolyte secondary battery, and a nickel-manganese composite hydroxide precursor thereof. A nickel-manganese composite hydroxide, which is formed by secondary particles formed by a plurality of primary particles agglomerated with each other, and is represented by the general formula (1): Ni x1 Mn y1 M z1 (OH) 2+α (satisfying 0.70≤x1≤0.95, 0.05≤y1≤0.30, x1+y1+z1=1.0 and 0≤α≤0.4, M is at least one element selected from Co, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, Fe, W.) indicates that there is a manganese-enriched layer from the particle surface to the inside of the particle of the secondary particle, and the manganese-enriched layer is represented by the general formula (2): Ni x2 Mn y2 M z2 (OH) 2+α It means that the thickness of the manganese-rich layer is 5% or more and 20% or less relative to the radius of the secondary particle.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of the patent application "Nickel-manganese composite hydroxide and its manufacturing method, positive electrode active material for non-aqueous electrolyte secondary battery and its manufacturing method, and non-aqueous electrolyte secondary battery" with the application date of October 31, 2017 and the application number of 201780081165.8. Technical Field

[0002] The present invention relates to a nickel-manganese composite hydroxide and a method for producing the same, a positive electrode active material for a non-aqueous electrolyte secondary battery and a method for producing the same, and a non-aqueous electrolyte secondary battery. Background Art

[0003] In recent years, with the popularity of portable electronic devices such as mobile phones and notebook personal computers, it is strongly desired to develop a small and lightweight non-aqueous electrolyte secondary battery with high energy density. As a representative example of such a non-aqueous electrolyte secondary battery, there is a lithium ion secondary battery. The negative electrode active material of the lithium ion secondary battery uses lithium metal, lithium alloy, metal oxide, or carbon. These materials are materials that can be deintercalated and embedded in lithium.

[0004] For lithium ion secondary batteries, research and development is currently prevalent. Among them, lithium transition metal composite oxides, especially lithium cobalt composite oxides (LiCoO2) which are easier to synthesize, are used for lithium ion secondary batteries in which positive electrode active materials can obtain a high voltage of 4V level, so it is expected to be put into practical use as a battery with high energy density. However, lithium cobalt composite oxides (LiCoO2) use rare and expensive cobalt compounds as raw materials, which is the reason for the increase in battery costs. Therefore, as positive electrode active materials, it is desirable to use substances other than lithium cobalt composite oxides (LiCoO2).

[0005] In addition, recently, lithium ion secondary batteries are not only expected to be used as small secondary batteries for portable electronic devices, but also to be used as large secondary batteries for power storage, electric vehicles, etc. Therefore, it is possible to reduce the cost of active materials and manufacture cheaper lithium ion secondary batteries, which can be expected to have an effect that will affect a wider range of fields. Therefore, for materials newly proposed as positive electrode active materials for lithium ion secondary batteries, lithium manganese composite oxides (LiMn2O4) using manganese that is cheaper than cobalt and lithium nickel composite oxides (LiNiO2) using nickel can be cited.

[0006] The raw materials of lithium manganese composite oxide (LiMn2O4) are cheap, and its thermal stability, especially its safety against fire, is excellent. Therefore, it can be said to be a powerful alternative material to lithium cobalt composite oxide (LiCoO2). However, its theoretical capacity is only about half of that of lithium cobalt composite oxide (LiCoO2), so it has the following disadvantages: it is difficult to meet the increasing demand for high capacity of lithium ion secondary batteries. In addition, it also has the following disadvantages: above 45°C, self-discharge is severe, and the charge and discharge life is also reduced.

[0007] On the other hand, lithium nickel composite oxide (LiNiO2) has a theoretical capacity that is substantially the same as that of lithium cobalt composite oxide (LiCoO2), and exhibits a slightly lower battery voltage than lithium cobalt composite oxide. Therefore, the problem of electrolyte decomposition due to oxidation is less likely to occur, and higher capacity can be expected, so development has been prevalent.

[0008] However, when a lithium nickel composite oxide composed purely of nickel without replacing nickel with other elements is used as a positive electrode active material to produce a lithium ion secondary battery, lithium ions are more easily deintercalated than other positive electrode materials, and there is a disadvantage of causing gelation when preparing a paste for producing battery plates.

[0009] In order to solve such a disadvantage, various solutions have been proposed. For example, Patent Document 1 proposes a LiNi-cobalt-manganese composite oxide having a water-soluble alkali content of 0.4 mass % or less as a lithium nickel cobalt manganese composite oxide synthesized with a good composition ratio balance. a Co b Mn c O2 (where a+b+c=1, 0.3≤a≤0.6, 0.3≤b≤0.6, 0.1≤c≤0.4).

[0010] In addition, for example, Patent Document 2 proposes a method for manufacturing a positive electrode active material for a lithium-ion battery, which is characterized in that, on the basis of a nickel-cobalt composite oxide and a lithium compound, one or more compounds selected from aluminum compounds, zirconium compounds, bismuth compounds and antimony compounds having an average primary particle size of less than 1 μm are mixed and roasted, and then lithium hydroxide and lithium carbonate are removed in an acidic aqueous solution and roasted again.

[0011] Furthermore, for example, Patent Document 3 proposes a positive electrode material for a non-aqueous electrolyte secondary battery, which is obtained by mixing and roasting a metal composite hydroxide with nickel as the main component and a lithium compound to optimize the composition, and then stirring with water. Thus, a positive electrode active material with high capacity, excellent cycle characteristics and less eluted alkali components can be obtained.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: Japanese Patent Application Publication No. 2011-076797

[0015] Patent Document 2: Japanese Patent Application Publication No. 2011-113885

[0016] Patent Document 3: Japanese Patent Application Publication No. 2015-056368 Summary of the invention

[0017] Problem that the invention aims to solve

[0018] However, the lithium nickel cobalt manganese composite oxide of the above-mentioned patent document 1 is a material with a nickel content of about 60% that is originally responsible for the redox reaction of charge and discharge, so it is difficult to achieve high capacity. In addition, for the positive electrode active material of the above-mentioned patent document 2, the process of acid-washing the calcined product and then calcining it again is complicated and costly, and there is also the problem of reduced capacity due to the addition of elements. Furthermore, for the positive electrode material of the above-mentioned patent document 3, since water stirring and drying processes are applied, it is costly, and it is difficult to optimize the water washing conditions, leaving the problem that the target capacity cannot be obtained when it is not within the optimal condition range.

[0019] In view of the above situation, the present invention aims to provide a positive electrode active material having high capacity and high energy density and reduced elution lithium amount when used in a non-aqueous electrolyte secondary battery and a nickel-manganese composite hydroxide as a precursor thereof. In addition, the present invention aims to provide a method for producing a nickel-manganese composite hydroxide that can be easily produced on an industrial scale and a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery using the nickel-manganese composite hydroxide.

[0020] Solutions for solving problems

[0021] In a first aspect of the present invention, there is provided a nickel-manganese composite hydroxide, which is formed of secondary particles formed by a plurality of primary particles agglomerated together, and is represented by the general formula (1): Ni x1 Mn y1 M z1 (OH) 2+α (In formula (1), 0.70≤x1≤0.95, 0.05≤y1≤0.30, x1+y1+z1=1.0 and 0≤α≤0.4 are satisfied, and M is at least one element selected from Co, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, Fe and W.) indicates that there is a manganese-enriched layer from the particle surface to the inside of the secondary particle, and the manganese-enriched layer is represented by the following general formula (2), and the thickness of the manganese-enriched layer is greater than 5% and less than 20% relative to the radius of the secondary particle.

[0022] General formula (2): Ni x2 Mn y2 M z2 (OH) 2+α

[0023] (In formula (2), x2+z2=0 and y2=1, or y2 / (x2+z2)≥0.6, 0≤z2≤0.40, x2+y2+z2=1.0, and 0≤α≤0.4 are satisfied, and M is at least one element selected from Co, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, Fe, and W.)

[0024] In addition, the nickel-manganese composite hydroxide is preferably such that, in the particle size distribution measured by the laser diffraction scattering method, the volume average particle size (Mv) is 4 μm or more and 20 μm or less, and the fluctuation index of the particle size calculated from the cumulative particle size (D90) of 90% by volume, the cumulative particle size (D10) of 10% by volume, and the volume average particle size (Mv) [(D90-D10) / Mv] is 0.60 or more. In addition, the nickel-manganese composite hydroxide is preferably such that the tap density is 1.8 g / cm 3 Above and 3.2g / cm 3 the following.

[0025] In the second embodiment of the present invention, a method for producing a nickel-manganese composite hydroxide is provided, which is the method for producing the above-mentioned nickel-manganese composite hydroxide, and comprises the following steps: a first crystallization step, which comprises the following steps: continuously supplying a first mixed aqueous solution containing at least a nickel salt and a manganese salt to a reaction aqueous solution, neutralizing and crystallizing it to generate particles of the nickel-manganese composite hydroxide, and allowing a slurry containing the particles to overflow from a reaction tank to recover the particles; and a second crystallization step, neutralizing and crystallizing the reaction aqueous solution containing the recovered particles and the second mixed aqueous solution to form a manganese-enriched layer on the surface of the particles, wherein the second mixed aqueous solution has a molar ratio of Ni, Mn and M that is the same as the molar ratio of Ni, Mn and M in the manganese-enriched layer.

[0026] In addition, it is preferred that the ammonia concentration of the reaction aqueous solution is adjusted to 5 g / L or more and 25 g / L or less in the first crystallization step and the second crystallization step. In addition, it is preferred that the temperature of the reaction aqueous solution is adjusted to a range of 35° C. or more and 60° C. or less in the first crystallization step and the second crystallization step. In addition, it is preferred that the pH value of the reaction aqueous solution measured based on a liquid temperature of 25° C. is adjusted to a range of 10.0 or more and 13.0 or less in the second crystallization step.

[0027] In a third embodiment of the present invention, there is provided a positive electrode active material for a non-aqueous electrolyte secondary battery, which is formed of a lithium nickel manganese composite oxide having a hexagonal layered structure, wherein the lithium nickel manganese composite oxide comprises secondary particles formed by a plurality of primary particles agglomerated with each other, and is represented by the general formula (3): Li 1+t Ni x3 Mn y3 M z3 O 2+β (In formula (3), -0.05≤t≤0.5, 0.70≤x3≤0.95, 0.05≤y3≤0.30, x3+y3+z3=1.0 and 0≤β≤0.5 are satisfied, and M is at least one element selected from Co, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, Fe and W.) It means that the circularity of the secondary particles calculated by image analysis is greater than 0.95, the crystallite diameter of the (003) plane determined based on X-ray diffraction is greater than 160nm and less than 300nm, and when immersed in water, the amount of lithium dissolved into water is less than 0.2% by mass relative to the total positive electrode active material.

[0028] In addition, the above-mentioned positive electrode active material is preferably that the volume average particle size (Mv) is 4 μm or more and 20 μm or less in the particle size distribution measured by the laser diffraction scattering method, and the fluctuation index of the particle size calculated by the cumulative 90 volume % particle size (D90) and the cumulative 10 volume % particle size (D10) and the volume average particle size (Mv) [(D90-D10) / Mv] is 0.60 or more. In addition, the above-mentioned positive electrode active material is preferably that the specific surface area is 0.20m 2 / g or more and 0.70m 2 / g or less. In addition, the positive electrode active material preferably has a tap density of 2.2 g / cm 3 Above and 3.6g / cm 3 the following.

[0029] In a fourth embodiment of the present invention, there is provided a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, wherein the positive electrode active material is composed of a lithium nickel manganese composite oxide having a hexagonal layered structure, and the lithium nickel manganese composite oxide is represented by the general formula (3): Li 1+t Ni x3 Mn y3 M z3 O 2+β(In formula (3), -0.05≤t≤0.5, 0.70≤x3≤0.95, 0.05≤y3≤0.30, x3+y3+z3=1.0 and 0≤β≤0.5 are satisfied, and M is at least one element selected from Co, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, Fe and W.) It means that the manufacturing method includes the following steps: mixing the above-mentioned nickel manganese composite hydroxide with a lithium compound to form a lithium mixture; and calcining the lithium mixture in an oxidizing atmosphere at a temperature of not less than 800°C and not more than 950°C to obtain a lithium nickel manganese composite oxide.

[0030] In addition, it is preferred that, in the particle size distribution measured by laser diffraction scattering method, the value obtained by dividing the cumulative 50 volume % particle size (D50) of the lithium nickel manganese composite oxide after calcination by the cumulative 50 volume % particle size (D50) of the nickel manganese composite hydroxide before calcination is 1.2 or less.

[0031] In a fifth aspect of the present invention, there is provided a nonaqueous electrolyte secondary battery comprising a positive electrode containing the positive electrode active material.

[0032] Effects of the Invention

[0033] According to the present invention, a positive electrode active material having high capacity and high energy density when used in a non-aqueous electrolyte secondary battery and having suppressed gelation in the paste preparation when manufacturing a battery plate and a nickel-manganese composite hydroxide serving as a precursor thereof can be obtained. In addition, the manufacturing method of the present invention can easily manufacture the above-mentioned positive electrode active material and the nickel-manganese composite hydroxide serving as a precursor thereof on an industrial scale, and it can be said that the industrial value is extremely high. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic diagram showing an example of the nickel-manganese composite hydroxide according to the embodiment.

[0035] Figure 2 1 is a flow chart showing an example of a method for producing a nickel-manganese composite hydroxide according to an embodiment.

[0036] Figure 3 It is a flowchart showing an example of the method for producing the positive electrode active material according to the embodiment.

[0037] Figure 4 (A) and Figure 4 (B) is a photograph showing an example of the appearance and cross section of the nickel-manganese composite hydroxide of Example 1, Figure 4 (C) and Figure 4 (D) is a photograph showing an example of the appearance and cross section of the nickel-manganese composite hydroxide of Comparative Example 1.

[0038] Figure 5 This is a schematic cross-sectional view of a coin-type battery used for evaluating battery characteristics. DETAILED DESCRIPTION

[0039] Hereinafter, the nickel-manganese composite hydroxide, the positive electrode active material for a non-aqueous electrolyte secondary battery, and the details of their manufacturing methods of the present embodiment will be described with reference to the accompanying drawings. In addition, in the accompanying drawings, in order to facilitate the understanding of each structure, a part is emphasized or a part is simplified, and the actual structure or shape, scale, etc. are sometimes different. It should be noted that in the specification, the description of "A to B" means "above A and below B".

[0040] 1. Nickel-manganese composite hydroxide

[0041] Figure 1 A schematic diagram showing an example of a nickel-manganese composite hydroxide 10 (hereinafter also referred to as "composite hydroxide 10") of the present embodiment. The composite hydroxide 10 includes a secondary particle 1 formed by a plurality of primary particles agglomerated with each other, and has a manganese-enriched layer 2 from the particle surface of the secondary particle to the inside of the particle. A central portion 3 is arranged inside the manganese-enriched layer 2. The composite hydroxide 10 has a multilayer structure in which the composition inside the secondary particle (central portion 3) is different from the composition of the peripheral portion (manganese-enriched layer 2), and the ratio of Mn in the composition of the peripheral portion (manganese-enriched layer 2) is high compared to the composition inside the secondary particle (central portion 3).

[0042] (Overall composition of nickel-manganese composite hydroxide)

[0043] The composite hydroxide 10 is represented by the general formula (1): Ni x1 Mn y1 M z1 (OH) 2+α (M is at least one element selected from Co, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, Fe and W, and satisfies x1 of 0.70≤x1≤0.95, y1 of 0.05≤y1≤0.30, and x1+y1+z1=1.0, and α of 0≤α≤0.4.) It should be noted that the above formula (1) represents the composition of the composite hydroxide 10 as a whole.

[0044] In the above formula (1), x representing the nickel content is greater than 0.7 and less than 0.95. When the composite hydroxide 10 is used as a precursor (raw material) to manufacture a positive electrode active material, the overall composition ratio (Ni:Mn:M) of the composite hydroxide 10 is also maintained in the obtained positive electrode active material. When the positive electrode active material obtained using the composite hydroxide 10 having such a composition as a precursor is used in a secondary battery, a high capacity can be achieved. In addition, the composition ratio of the composite hydroxide 10 is adjusted so that it becomes the same as the composition ratio required for the desired positive electrode active material.

[0045] In addition, in the above formula (1), z representing the content of M is greater than 0 and less than 0.25. When Co is included as M, the power characteristics and cycle characteristics are further improved. In addition, the Mn / Ni ratio of the entire composite hydroxide 10 is greater than 0.05 and less than 0.42, and from the perspective of obtaining a high battery capacity, it can be less than 0.35 or less than 0.3. It should be noted that in the above formula (1), α is a coefficient that varies according to the valence of the metal element contained in the composite hydroxide 10.

[0046] (Particle structure of nickel-manganese composite hydroxide)

[0047] For the discharge capacity of a secondary battery manufactured with lithium nickel manganese composite oxide (hereinafter also referred to as "lithium composite oxide") as the positive electrode active material, the more Ni content (i.e., the higher the Mn / Ni), the higher the capacity and the better the performance, but it is known that when the Ni content is high, the alkalinity becomes high, and gelation is easily produced when preparing the positive electrode composite material paste. In addition, as described in Patent Document 3, the lithium dissolved from the positive electrode active material is said to be one of the factors of the gelation of the positive electrode composite material paste, especially in lithium composite oxides with a high Ni content, it is sometimes necessary to adjust the process of dissolving the lithium amount. It should be noted that the amount of dissolved lithium refers to the amount of lithium that can be dissolved into water in the lithium composite oxide, and refers to the amount of excess lithium such as excess lithium from unreacted lithium compounds in the lithium composite oxide and excess lithium in the crystals of the lithium composite oxide.

[0048] On the other hand, the present inventors have refocused on the following situation: in the manufacturing process of lithium composite oxide, i) the degree of sintering during calcination is related to the Mn / Ni ratio. If the Mn / Ni ratio is low, the degree of sintering increases, and conversely, if the Mn / Ni ratio is high, the degree of sintering decreases; further, ii) the amount of dissolved lithium is related to the calcination temperature. If the calcination temperature is high, the amount of dissolved lithium decreases, and conversely, if the calcination temperature is low, the amount of dissolved lithium increases. They found that: as a precursor of lithium nickel manganese composite oxide, a precursor having a structure in which the Mn / Ni ratio of the entire nickel manganese composite hydroxide is low (that is, the Ni content is high, and the Mn / Ni ratio of only the surface is high (that is, the Mn content is high) is used, and the calcination conditions of the precursor and the lithium compound are adjusted, so that a positive electrode active material with higher capacity and high energy density and capable of suppressing gelation of the positive electrode composite material paste can be obtained, and the present invention has been completed.

[0049] The composite hydroxide 10 of this embodiment has a multilayer structure in which the composition of the central portion 3 is different from the composition of the manganese-rich layer 2 of the peripheral portion, and can be adjusted in a manner such that the Mn / Ni content ratio of the composition of the manganese-rich layer 2 is higher than that of the composition of the central portion 3. Thus, the composite hydroxide 10 reduces the amount of dissolved lithium and suppresses sintering within a moderate range by adjusting the roasting temperature, thereby obtaining a positive electrode active material having a higher capacity and a high energy density and being able to suppress the gelation of the positive electrode composite material paste. The roasting temperature can be set to, for example, above 800°C. On the other hand, as shown in the above formula (1), the composite hydroxide 10 has a high ratio of Ni in the overall composition of the secondary particles, and therefore, a positive electrode active material using the composite hydroxide 10 as a precursor can be used to make a high-capacity secondary battery.

[0050] The manganese-rich layer 2 is represented by the following general formula (2).

[0051] General formula (2): Ni x2 Mn y2 M z2 (OH) 2+α

[0052] (In formula (2),

[0053] Satisfies x2+z2=0 and y2=1, or satisfies y2 / (x2+z2)≥0.6,

[0054] Satisfies 0≤z2≤0.40, x2+y2+z2=1.0, and 0≤α≤0.4,

[0055] M is at least one element selected from Co, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, Fe and W. )

[0056] The manganese-rich layer 2 may contain Mn alone as a metal. In the above case, in the above formula (2), x2+z2=0, y2=1 is satisfied, and the composition of the manganese-rich layer 2 is Mn(OH) 2+α In addition, the manganese-rich layer 2 may contain at least one of Ni and M as a metal other than Mn. In the above case, in the above formula (2), y / (x+z)≥0.6 is satisfied, and the manganese-rich layer 2 contains Mn in an amount of 0.6 times or more relative to the total amount (molar) of Ni and M.

[0057] When the manganese-rich layer 2 contains a metal other than Mn, in the above formula (2), x2 representing the content of nickel is preferably 0.2 or more, preferably 0.35 or more, and more preferably 0.4 or more from the viewpoint of obtaining a higher battery capacity. In addition, in the above formula (2), z2 representing the content of the element M is a value that can be appropriately adjusted according to the desired battery characteristics, and is 0 or more and 0.4 or less, and may be 0.3 or less, or 0.2 or less.

[0058] When the composition of the manganese-rich layer 2 satisfies the above formula (2), excessive sintering when the calcination temperature is increased can be suppressed in the production process of the lithium composite oxide, and the amount of dissolved lithium can be reduced. In addition, as described later, the obtained lithium composite oxide has high circularity, high packing properties, and high energy density.

[0059] It should be noted that the composition of the manganese-rich layer 2 can be obtained, for example, by quantitative analysis of energy dispersive X-ray analysis (EDX) in cross-sectional observation using a scanning electron microscope. In addition, the composition of the manganese-rich layer 2 can be adjusted to a desired range by controlling the composition of the metal component of the second mixed aqueous solution in the second crystallization step (step S2) as described later.

[0060] The thickness t of the manganese-rich layer 2 is 5% or more and 20% or less, preferably 5% or more and 15% or less, and more preferably 5.5% or more and 10% or less relative to the radius r of the secondary particle 1. By adjusting the thickness t of the manganese-rich layer 2 to the above range, sintering when the calcination temperature is increased can be suppressed. The thickness t of the manganese-rich layer 2 can be calculated, for example, as follows: when observing the cross section of the secondary particle at a magnification of 1000 times using a scanning electron microscope (SEM), 20 secondary particles having a volume average particle diameter of 80% to 120% relative to the volume average particle diameter (Mv) calculated from the particle size distribution measured by the laser diffraction scattering method are randomly selected, and the average value of the ratio (%) of the thickness of each manganese-rich layer 2 relative to the radius r of the secondary particle is calculated.

[0061] It should be noted that the number of layers of the manganese-rich layer 2 is not particularly limited. Figure 1As shown, it may be a single layer or multiple layers. When the manganese-rich layer 2 is formed of multiple layers, the thickness t of the manganese-rich layer 2 refers to the total thickness of the multiple layers.

[0062] (Volume average particle size of nickel-manganese composite hydroxide)

[0063] The particle size of the composite hydroxide 10 is not particularly limited and can be set to a desired range. When the composite hydroxide 10 is used as a precursor of a positive electrode active material, the volume average particle size (Mv) of the composite hydroxide 10 is preferably 5 μm or more and 20 μm or less, more preferably 6 μm or more and 15 μm or less. When the volume average particle size (Mv) is less than 5 μm, the filling property of the obtained lithium composite oxide is greatly reduced, and it is sometimes difficult to increase the battery capacity per unit volume when used as a positive electrode active material. On the other hand, when the volume average particle size (Mv) exceeds 20 μm, the filling property will not be greatly deteriorated, but the specific surface area is reduced, so the reactivity with the lithium raw material is reduced when the positive electrode active material is made, and a positive electrode active material with high battery characteristics cannot be obtained. In addition, when the volume average particle size (Mv) is too large, the cycle characteristics of the obtained positive electrode active material are reduced, and the interface with the electrolyte is reduced, so the resistance of the positive electrode increases, and the power characteristics of the battery are sometimes reduced. It should be noted that the volume average particle size (Mv) can be measured using a laser diffraction scattering particle size analyzer.

[0064] (Particle size distribution of nickel-manganese composite hydroxide)

[0065] For the composite hydroxide 10, the index representing the amplitude of the particle size distribution, namely [(D90-D10) / average particle size], is preferably greater than 0.60, can be greater than 0.7, and can also be greater than 0.8. When [(D90-D10) / average particle size] of the composite hydroxide 10 is within the above range, the particle filling property is improved, and when the composite hydroxide 10 is used as a precursor of a positive electrode active material, the volume energy density of the positive electrode active material of the resulting secondary battery can be made higher. [(D90-D10) / average particle size] can be adjusted, for example, as follows: composite hydroxides with different particle sizes are mixed, or composite hydroxides are manufactured using a continuous crystallization method, so that it can be adjusted to the above range. As described later, when the composite hydroxide 10 (especially the center portion 3) is formed using a continuous crystallization method, it can be easily adjusted to the above range. It should be noted that from the viewpoint of suppressing excessive mixing of fine particles or coarse particles into the composite hydroxide 10, the upper limit of [(D90-D10) / average particle size] is preferably less than 1.2.

[0066] In the index representing the amplitude of the particle size distribution, namely [(D90-D10) / average particle size], d10 refers to the particle size at which the number of particles in each particle size is accumulated from the smaller particle size side, and the cumulative volume becomes 10% of the total volume of all particles. In addition, D90 refers to the particle size at which the cumulative volume becomes 90% of the total volume of all particles when the number of particles is accumulated in the same way. The average particle size, D90, and D10 can be calculated from the volume integral value measured using a laser diffraction scattering particle size analyzer. As the average particle size, the volume average particle size (Mv) is used. It should be noted that the volume average particle size (Mv), D90, and D10 can be measured using a laser diffraction scattering particle size analyzer.

[0067] It should be noted that the composite hydroxide 10 is composed of secondary particles formed by agglomeration of a plurality of primary particles, and may include a small amount of single primary particles such as primary particles that are not aggregated as secondary particles and primary particles that fall off from secondary particles after aggregation.

[0068] (Tap density of nickel-manganese composite hydroxide)

[0069] The composite hydroxide 10 preferably has a tap density of 1.8 g / cm 3 Above and 3.2g / cm 3 When the tap density is within the above range, the fillability of the obtained positive electrode active material is more excellent, and the volume energy density of the positive electrode active material of the secondary battery using the positive electrode active material can be higher. It should be noted that the tap density can be set to the above range by adjusting the particle size distribution of the average particle size of the composite hydroxide 10.

[0070] 2. Method for producing nickel-manganese composite hydroxide

[0071] The method for producing the nickel manganese composite hydroxide of the present embodiment may employ any method as long as it can produce the composite hydroxide 10 having a multilayer structure in which the composition of the secondary particle interior 3 is different from the composition of the manganese-rich layer 2 (peripheral portion).

[0072] As a method for manufacturing the composite hydroxide 10, for example, there are the following methods: method 1), after forming particles of the composite hydroxide (central portion 3) by a continuous crystallization method, a manganese-rich layer 2 is formed by crystallization; method 2), by a two-step intermittent crystallization method, the particles of the composite hydroxide (central portion 3) and the manganese-rich layer 2 are sequentially manufactured; method 3), after forming particles of the composite hydroxide (central portion 3) by a spray drying method, a spray pyrolysis method, etc., a manganese-rich layer 2 is formed by crystallization; method 4), after forming particles of the composite hydroxide (central portion 3) by an intermittent crystallization method, a continuous crystallization method, a spray drying method, a spray pyrolysis method, etc., a manganese-rich layer 2 is formed by mechanical coating, etc.

[0073] Among them, as a method for manufacturing a composite hydroxide 10, the above method 1) is the best, that is, after forming particles (central portion 3) of a composite hydroxide by a continuous crystallization method, a manganese-enriched layer 2 is formed by crystallization. Here, the continuous crystallization method refers to the following crystallization method: while continuously supplying a mixed aqueous solution containing a metal salt, a neutralizing agent is supplied, the pH is controlled and particles of a composite hydroxide are generated, and the composite hydroxide particles are recovered by overflow. Compared with the intermittent crystallization method, the continuous crystallization method is easy to obtain particles with a wide particle size distribution and secondary particles with high filling properties. In addition, the continuous crystallization method is suitable for mass production and has also become an advantageous manufacturing method in industry.

[0074] For example, as described in 1) above, when the particles (center portion 3) of the composite hydroxide are formed by a continuous crystallization method, the filling property (tap density) of the obtained composite hydroxide 10 can be further improved, and a composite hydroxide 10 having a higher filling density and a high energy density can be produced simply and in large quantities. An example of a manufacturing method using the manufacturing method described in 1) above is described below.

[0075] Figure 2 FIG. 1 is a flow chart showing an example of a method for producing the composite hydroxide 10. Figure 2 It is appropriate to refer to the flowchart for explanation Figure 1 First, particles (central portion 3) of nickel-manganese composite hydroxide are formed by continuous crystallization, and the generated particles (central portion 3) are recovered (step S1). Next, the recovered particles are mixed with a second mixed aqueous solution having the same molar ratio of Ni, Mn and M as that in the manganese-rich layer, and the mixture is neutralized and crystallized to form a manganese-rich layer 2 (step S2). Each step is described below.

[0076] (1) First crystallization step

[0077] In the first crystallization step, first, a first mixed aqueous solution containing at least a nickel salt and a manganese salt is continuously supplied to the reaction aqueous solution to neutralize and crystallize the solution to generate particles of nickel-manganese composite hydroxide. It should be noted that in the first crystallization step, the central portion 3 of the composite hydroxide 10 is mainly formed. Next, the slurry containing the particles of nickel-manganese composite hydroxide (central portion 3) is overflowed from the reaction tank to recover the particles of nickel-manganese composite hydroxide.

[0078] As a specific scheme of the first crystallization step, for example, a first mixed aqueous solution containing at least a nickel salt and a manganese salt in a reaction tank is stirred at a constant speed while a neutralizing agent (e.g., an alkaline solution, etc.) is added to neutralize the solution, thereby controlling the pH, and generating particles of a nickel-manganese composite hydroxide (including secondary particles corresponding to the center portion 3) by coprecipitation. It should be noted that a complexing agent may be added arbitrarily together with the neutralizing agent. The following describes each component.

[0079] (First mixed aqueous solution)

[0080] The first mixed aqueous solution may use an aqueous solution in which at least a nickel salt and a manganese salt are dissolved. Furthermore, the first mixed aqueous solution may contain at least one element selected from Co, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, Fe and W (hereinafter also referred to as "element M"), or an aqueous solution in which a nickel salt, a manganese salt and a salt containing M are dissolved may be used. As the nickel salt, the manganese salt and the salt containing the element M, for example, at least one selected from the group consisting of sulfate, nitrate and chloride may be used. Among them, from the viewpoint of cost and waste liquid treatment, sulfate is preferably used.

[0081] The concentration of the first mixed aqueous solution is preferably set to 1.0 mol / L or more and 2.4 mol / L or less, and more preferably set to 1.2 mol / L or more and 2.2 mol / L or less, based on the sum of the dissolved metal salts. When the concentration of the first mixed aqueous solution is less than 1.0 mol / L based on the sum of the dissolved metal salts, the concentration is too low, so there is a concern that the primary particles constituting the composite hydroxide cannot grow fully. On the other hand, when the concentration of the first mixed aqueous solution exceeds 2.4 mol / L, it exceeds the saturation concentration at room temperature, so crystals precipitate again, and there is a concern about clogging the piping. In addition, when the concentration of the first mixed aqueous solution is too high, the amount of nucleation of the primary particles increases, and there is a concern that the ratio of microparticles in the slurry containing the particles of the obtained composite hydroxide increases. Here, the composition of the metal elements contained in the first mixed aqueous solution is consistent with the composition of the metal elements contained in the particles (central portion 3) of the obtained composite hydroxide. Therefore, the composition of the metal elements of the mixed aqueous solution can be modulated so that it becomes the same as the composition of the metal elements of the central portion 3 of the target composite hydroxide 10. The composition of the metal element in the center portion 3 is not particularly limited as long as it is within a range that can provide the composite hydroxide 10 represented by the above formula (1) when the manganese-rich layer represented by the above formula (2) is finally present.

[0082] (Neutralizer)

[0083] The neutralization of the first mixed aqueous solution can be carried out by adding a neutralizing agent. As a neutralizing agent, an alkaline solution can be used, for example, an aqueous solution of an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide can be used. Among them, from the viewpoint of cost and ease of operation, an aqueous sodium hydroxide solution is preferably used. It should be noted that the alkali metal hydroxide can be directly added to the reaction aqueous solution and neutralized. From the perspective of the difficulty of pH control, it is preferably added in the form of an aqueous solution. In the above case, the concentration of the aqueous solution of the alkali metal hydroxide is preferably set to 12% by mass or more and 30% by mass or less, and more preferably set to 20% by mass or more and 30% by mass or less. When the concentration of the aqueous solution of the alkali metal hydroxide is lower than 12% by mass, the supply amount to the reaction tank increases, and there is a concern that the particles cannot grow fully. On the other hand, when the concentration of the aqueous solution of the alkali metal hydroxide exceeds 30% by mass, the pH value locally increases at the addition position of the alkali metal hydroxide, and there is a concern that microparticles will be generated.

[0084] (Complexing agent)

[0085] The complexing agent is not particularly limited, as long as it can be combined with metal elements such as nickel ions and manganese ions in aqueous solution to form a complex. For example, an ammonium ion donor can be cited as a complexing agent. As the ammonium ion donor, it is not particularly limited, for example, at least one selected from the group consisting of ammonia water, ammonium sulfate aqueous solution and ammonium chloride aqueous solution can be used. Wherein, from the ease of operation, preferably ammonia water is used. When using an ammonium ion donor, it is preferred to make the concentration of ammonium ions in the range of more than 5g / L and less than 25g / L.

[0086] (pH Control)

[0087] In the first crystallization step, the pH value of the reaction aqueous solution is controlled so that it is in the range of 11.0 to 13.0, preferably 12.0 to 13.0, based on a liquid temperature of 25°C. When the pH value exceeds 13.0, the growth rate of the primary particles is fast, and it becomes easy to cause nucleation, so the secondary particles obtained tend to be small in size and poor in sphericity. On the other hand, when the pH value is lower than 11.0, the generation rate of the composite hydroxide is significantly slowed down, nickel remains in the filtrate, and the composition of the particles (center portion 3) of the obtained composite hydroxide sometimes deviates significantly from the target value.

[0088] It should be noted that the particle size of the composite hydroxide 10 can be controlled to a desired range mainly by appropriately adjusting the particle size of the center portion 3. The particle size of the center portion 3 can be controlled to a desired range, for example, by appropriately adjusting the pH value in the first crystallization step (continuous crystallization step) within the above range.

[0089] (Reaction atmosphere)

[0090] In the first crystallization step, from the viewpoint of suppressing the oxidation of manganese and the like and stably generating primary particles and secondary particles, the oxygen concentration in the space in the reaction tank can be controlled to preferably be 10% by volume or less, more preferably 5% by volume or less, and further preferably 3% by volume or less. The oxygen concentration in the atmosphere can be adjusted using, for example, an inert gas such as nitrogen or argon. As a means for adjusting the oxygen concentration in the atmosphere to a specified concentration, for example, a constant amount of atmosphere gas can be continuously circulated in the atmosphere.

[0091] (Reaction temperature)

[0092] In the first crystallization step, the temperature of the aqueous solution (reaction aqueous solution) in the reaction tank is preferably in the range of 35°C or more and 60°C or less, and more preferably in the range of 40°C or more and 55°C or less. When the temperature of the reaction aqueous solution exceeds 60°C, the priority of nucleation is increased compared with particle growth in the reaction aqueous solution in the reaction tank, and the shape of the primary particles constituting the composite hydroxide 10 (mainly the center 3) tends to become excessively fine. If such a composite hydroxide 10 is used, there is a problem that the filling property of the obtained positive electrode active material becomes low. On the other hand, when the temperature of the reaction aqueous solution is lower than 35°C, there is a tendency for particle growth to take precedence over nucleation in the reaction aqueous solution, and therefore, the shapes of the primary particles and secondary particles constituting the composite hydroxide 10 (mainly the center 3) tend to become coarse. When the composite hydroxide 10 having such coarse secondary particles is used as a precursor of the positive electrode active material, a positive electrode active material containing very large coarse particles that produce concave and convex when the electrode is made is sometimes formed. Furthermore, when the reaction aqueous solution is lower than 35° C., the amount of metal ions remaining in the reaction aqueous solution is high, the reaction efficiency is extremely poor, and a composite hydroxide containing a large amount of impurity elements is likely to be generated.

[0093] (2) Second Crystallization Step

[0094] In the second crystallization step, the reaction aqueous solution containing the particles of the composite hydroxide recovered above (central portion 3) and the second mixed aqueous solution is neutralized and crystallized to form a manganese-enriched layer 2 on the surface of the particles of the composite hydroxide (central portion 3). The second mixed aqueous solution contains at least a manganese salt and has the same molar ratio of Ni, Mn and M as that in the manganese-enriched layer 2.

[0095] As a specific scheme of the second crystallization step, for example, after the first crystallization step is completed, the recovered composite hydroxide particles (center 3) are transferred to different reaction tanks, and the aqueous solution containing the composite hydroxide particles (center 3) is stirred at a constant speed while adding and neutralizing the second mixed aqueous solution containing at least manganese (Mn) and a neutralizer (such as an alkaline solution, etc.), thereby controlling the pH and causing the manganese-enriched layer 2 to crystallize on the surface of the composite hydroxide particles (center 3). It should be noted that a complexing agent can be added arbitrarily together with the neutralizer. Below, each component is described.

[0096] (Second mixed aqueous solution)

[0097] The second mixed aqueous solution may use an aqueous solution containing at least a manganese salt. Furthermore, the second mixed aqueous solution may contain a nickel salt and a salt of element M, and an aqueous solution in which a nickel salt, a manganese salt and a salt containing M are dissolved may be used. As the nickel salt, the manganese salt and the salt containing M, for example, at least one selected from the group consisting of sulfates, nitrates and chlorides may be used. Among them, sulfates are preferably used from the viewpoints of cost and waste liquid treatment.

[0098] The concentration of the second mixed aqueous solution is preferably set to 1.0 mol / L or more and 2.4 mol / L or less, and more preferably set to 1.2 mol / L or more and 2.2 mol / L or less, based on the total amount of dissolved metal salts. When the concentration of the second mixed aqueous solution is less than 1.0 mol / L based on the total amount of dissolved metal salts, the concentration is too low, and therefore, there is a concern that the manganese-rich layer 2 cannot fully grow on the surface of the particles (central portion 3) of the composite hydroxide. On the other hand, when the concentration of the second mixed aqueous solution exceeds 2.4 mol / L, it exceeds the saturation concentration at room temperature, and therefore, there is a risk of crystal re-precipitation, clogging of the piping, etc. In addition, in the above case, the amount of nucleation of primary particles increases, and there is a concern that the manganese-rich layer 2 cannot fully grow on the surface of the particles (central portion 3) of the composite hydroxide. Here, the composition of the metal elements contained in the second mixed aqueous solution is consistent with the composition of the metal elements contained in the obtained manganese-rich layer. Therefore, the composition of the metal elements of the second mixed aqueous solution can be modulated to be the same as the composition of the metal elements of the target manganese-rich layer 2 (the molar ratio of Ni, Mn and M). The content ratio of the metal element in the second mixed solution includes Mn alone, or the content (molar) of Mn is 0.6 times or more the total amount (molar) of Mn, Ni and M.

[0099] (Neutralizer)

[0100] The neutralization of the second mixed aqueous solution can be carried out by adding a neutralizing agent. As a neutralizing agent, an alkaline solution can be used, for example, an aqueous solution of an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide can be used. Among them, from the viewpoint of cost and ease of operation, an aqueous sodium hydroxide solution is preferably used. It should be noted that an alkali metal hydroxide can be directly added to the reaction aqueous solution for neutralization, and from the perspective of the difficulty of pH control, it is preferably added in the form of an aqueous solution. In the above case, the concentration of the aqueous solution of the alkali metal hydroxide is preferably set to 12% by mass or more and 30% by mass or less, and more preferably set to 20% by mass or more and 30% by mass or less. When the concentration of the aqueous solution of the alkali metal hydroxide is less than 12% by mass, the supply amount to the reaction tank increases, and there is a concern that the particles cannot grow fully. On the other hand, when the concentration of the aqueous solution of the alkali metal hydroxide exceeds 30% by mass, the pH value locally increases at the addition position of the alkali metal hydroxide, and there is a concern that microparticles are generated.

[0101] (Complexing agent)

[0102] The complexing agent is not particularly limited, as long as it can be combined with metal elements such as nickel ions and manganese ions in aqueous solution to form a complex. For example, an ammonium ion donor can be cited as a complexing agent. As the ammonium ion donor, it is not particularly limited, for example, at least one selected from the group consisting of ammonia water, ammonium sulfate aqueous solution and ammonium chloride aqueous solution can be used. Wherein, from the ease of operation, preferably ammonia water is used. When using an ammonium ion donor, it is preferred to make the concentration of ammonium ions in the range of more than 5g / L and less than 25g / L.

[0103] (pH Control)

[0104] In the second crystallization step (crystallization coating step), the pH of the reaction aqueous solution is controlled so as to be in the range of 10.0 to 13.0, preferably 11.0 to 12.0, based on a liquid temperature of 25°C. When the pH value exceeds 13.0, nucleation is likely to occur, and therefore, it is difficult to form a manganese-rich layer 2 on the surface of the composite hydroxide particles (center 3). On the other hand, when the pH value is lower than 10.0, the generation rate of the manganese-rich layer 2 is significantly slowed, nickel and the like remain in the filtrate, and the composition of the manganese-rich layer 2 sometimes deviates significantly from the target value.

[0105] The thickness t of the manganese-rich layer 2 can be controlled by the supply amount of the metal element in the second crystallization step. Therefore, the supply amount of the second mixed aqueous solution can be appropriately adjusted so that the manganese-rich layer 2 becomes the desired thickness. At this time, the composition (overall) of the composite hydroxide 10 finally obtained according to the supply amount of the second mixed aqueous solution changes. Therefore, in order to thicken the film thickness of the manganese-rich layer 2 with the same composition (overall), the Mn content of the second mixed aqueous solution supplied in the second crystallization step (crystallization coating step) can be adjusted to a lower level, and on this basis, the supply amount of the second mixed aqueous solution can be increased. On the contrary, in order to reduce the film thickness of the manganese-rich layer 2 with the same composition (overall), the Mn content of the second mixed aqueous solution supplied in the second crystallization step (crystallization coating step) can be adjusted to a higher level, and on this basis, the supply amount of the second mixed aqueous solution can be reduced.

[0106] (Reaction atmosphere)

[0107] From the viewpoint of suppressing oxidation of manganese and the like and stably generating primary particles and secondary particles constituting the manganese-rich layer 2, the oxygen concentration in the space of the reaction tank is preferably controlled to be 10% by volume or less, more preferably 5% by volume or less, and further preferably 3% by volume or less. The preparation of the oxygen concentration in the atmosphere can be carried out by the same method as in the first crystallization step described above.

[0108] (Reaction temperature)

[0109] The temperature of the reaction aqueous solution is preferably in the range of 35° C. to 60° C., as in the first crystallization step, and more preferably in the range of 40° C. to 55° C. When the temperature of the reaction aqueous solution exceeds 60° C., the priority of nucleation is increased over particle growth in the reaction aqueous solution in the reaction tank, and the shape of the primary particles constituting the manganese-rich layer 2 becomes excessively fine. On the other hand, when the temperature of the reaction aqueous solution is lower than 35° C., there is a tendency that particle growth takes precedence over nucleation in the reaction aqueous solution, and therefore the shapes of the primary particles and secondary particles constituting the manganese-rich layer 2 tend to become coarse.

[0110] (3) Cleaning process

[0111] In addition, the manufacturing method of the present embodiment may include a cleaning process after the second crystallization process. The cleaning process is a process for cleaning the impurities contained in the composite hydroxide 10 obtained in the second crystallization process. As a cleaning solution, pure water is preferably used. In addition, the amount of the cleaning solution is preferably 1L or more relative to 300g of the composite hydroxide 10. When the amount of the cleaning solution is less than 1L relative to 300g of the composite hydroxide 10, the cleaning becomes insufficient, and impurities sometimes remain in the composite hydroxide 10. As a cleaning method, for example, a cleaning solution such as pure water can be passed through a filter such as a filter press. In the case of wanting to further clean the SO4 remaining in the composite hydroxide 10, as a cleaning solution, sodium hydroxide, sodium carbonate, etc. are preferably used.

[0112] 3. Positive electrode active materials for non-aqueous electrolyte secondary batteries

[0113] The positive electrode active material of this embodiment is composed of a lithium nickel manganese composite oxide (hereinafter also referred to as a "lithium metal composite oxide"), wherein the lithium nickel manganese composite oxide includes secondary particles formed by aggregation of primary particles and is represented by the general formula (3): Li 1+ t Ni x3 Mn y3 M z3 O 2+β (satisfying -0.05≤t≤0.5, 0.70≤x3≤0.95, 0.05≤y3≤0.30, x3+y3+z3=1.0 and 0≤β≤0.5, M is at least one element selected from Co, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, Fe and W.) In addition, the lithium metal composite oxide has a hexagonal layered structure.

[0114] In the above formula (3), x3 representing the content of Ni is greater than 0.70 and less than 0.95. When the content of Ni is within the above range, the secondary battery using the lithium metal composite oxide as the positive electrode active material has a high battery capacity. In addition, in the above formula (3), (1+t) representing the content of Li is greater than 0.95 and less than 1.50, preferably greater than 0.95 and less than 1.20.

[0115] In the above formula (3), y3 representing the content of Mn is greater than or equal to 0.05 and less than or equal to 0.30. The positive electrode active material of this embodiment is prepared by using a composite hydroxide 10 having a manganese-enriched layer as a precursor, so that, as described later, compared with a conventional positive electrode active material containing the same degree of Mn, the circularity is high, and the packing property and energy density can be excellent.

[0116] In the above formula (3), M is at least one element selected from Co, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, Fe and W, and z3 representing the content of M can be set to be greater than 0 and less than 0.25. When M contains Co, for example, the power characteristics and cycle characteristics are excellent. It should be noted that in the above formula (3), β is a coefficient that varies according to the valence of the metal element other than lithium contained in the lithium metal composite oxide and the ratio of lithium to the number of atoms of the metal element other than lithium. In addition, the composition of the above-mentioned Ni, Mn and element M of the positive electrode active material can be adjusted to the above range by adjusting the composition ratio of the composite oxide 10 as described above.

[0117] For the positive electrode active material, the circularity of the secondary particles calculated by image analysis is greater than 0.95. When the circularity is within the above range, the secondary particles are less sintered and aggregated with each other, and a high tap density is reflected. Therefore, the filling property is improved, and a secondary battery with a high energy density can be obtained. The upper limit of the circularity is not particularly limited, but is less than 1.00. The circularity of the positive electrode active material can be adjusted to the above range by using a composite hydroxide 10 having a manganese-enriched layer represented by the above formula (2) as a precursor and calcining it at a calcination temperature described later.

[0118] It should be noted that the circularity is calculated using a flow particle image analyzer (FPIA-3000 manufactured by Sysmex). The above device can be as follows: a small amount of sample is added to an aqueous or non-aqueous solution and introduced into the device as a suspension, so that the secondary particle images in the suspension can be continuously photographed and analyzed. The circularity is calculated by the projected area and perimeter of each secondary particle photographed using the following formula.

[0119] E=4πS / L 2 ···(Mode)

[0120] (In the above formula, E is the circularity, S is the projected area of ​​the secondary particle, L is the circumference of the secondary particle, and π is the circumference.)

[0121] In addition, for the positive electrode active material, the (003) surface crystallite diameter measured based on X-ray diffraction is 160 nm or more and 300 nm or less, preferably 160 nm or more and 200 nm or less. When the crystallite diameter is in the above range, the crystallinity of the positive electrode active material is high, and the battery capacity and power characteristics become excellent. The crystallite diameter of the positive electrode active material of the present embodiment can be adjusted to the above range by slowly diffusing the manganese in the manganese-enriched layer of the composite hydroxide 10 into the interior of the particles in the roasting process (step S4) described later.

[0122] In addition, for the positive electrode active material, the amount of lithium dissolved into the water (dissolved Li amount) is less than 0.2% by mass relative to the positive electrode active material as a whole. When the amount of Li dissolved is within the above range, when preparing the positive electrode composite material paste, the crosslinking of the binder is suppressed, and the gelation of the paste can be prevented. The amount of dissolved Li can be adjusted to the above range by calcining a lithium mixture containing a composite hydroxide 10 having a manganese-enriched layer on the surface at a high temperature (e.g., above 800°C). It should be noted that the lower limit of the dissolved Li is, for example, 0.0005% by mass or more. In addition, the amount of dissolved Li can be adjusted to the extent that the gelation can be suppressed when adjusting the desired positive electrode composite material paste. Depending on the conditions, it can be 0.01% by mass or more and 0.15% by mass or less, or it can be 0.05% by mass or more and 0.12% by mass or less. The amount of eluted Li can be measured as follows: 20 g of the obtained positive electrode active material is taken out, immersed in 100 cc of pure water at 25° C., stirred for 30 minutes, left to stand for 10 minutes, and the obtained supernatant is neutralized and titrated with an aqueous HCl solution.

[0123] For the positive electrode active material, in the particle size distribution measured by the laser diffraction scattering method, the volume average particle size (Mv) is greater than 4 μm and less than 20 μm. In addition, the positive electrode active material is preferably calculated from the cumulative 90 volume % particle size (D90) and the cumulative 10 volume % particle size (D10) and the volume average particle size (Mv), and the particle size fluctuation index [(D90-D10) / Mv] is greater than 0.60. When the fluctuation index is within the above range, the filling property is good and a high tap density is reflected. Therefore, the positive electrode active material has a high energy density. It should be noted that from the viewpoint of suppressing excessive mixing of fine particles or coarse particles into the positive electrode active material, the upper limit of [(D90-D10) / average particle size] is preferably less than 1.2.

[0124] For the positive electrode active material, the specific surface area is preferably 0.20 m 2 / g or more and 0.70m 2 / g or less, more preferably 0.30 m 2 / g or more and 0.50m 2 / g or less. If the specific surface area is less than 0.20m 2 / g, the contact area between the positive electrode active material and the electrolyte becomes smaller, resulting in deterioration of power characteristics. On the other hand, if the specific surface area exceeds 0.70m 2 When the amount is less than 1.0 / g, the contact area with moisture in the atmosphere increases, so that the weather resistance deteriorates and gelation is easily caused during the preparation of the paste.

[0125] The tap density of the positive electrode active material is preferably 2.2 g / cm 3 Above and 3.6g / cm3 Below, more preferably 2.3g / cm 3 Above and 3.6g / cm 3 When the tap density is within the above range, the positive electrode active material has both excellent battery capacity and filling properties, and the energy density of the battery can be further improved.

[0126] It should be noted that the positive electrode active material is composed of secondary particles formed by the aggregation of multiple primary particles, and may also include: primary particles that are not aggregated in the form of secondary particles; primary particles that fall off from the secondary particles after aggregation, etc. A small amount of individual primary particles. In addition, the positive electrode active material may include lithium metal composite oxides other than the lithium metal composite oxide of this embodiment within the range that does not hinder the effect of the present invention.

[0127] 4. Method for producing positive electrode active material for non-aqueous electrolyte secondary battery

[0128] The method for producing a positive electrode active material in this embodiment is a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, which is composed of a lithium nickel manganese composite oxide formed by secondary particles formed by aggregation of primary particles. The lithium nickel manganese composite oxide is represented by the general formula (3): Li 1+t Ni x3 Mn y3 M z3 O 2+β (satisfying -0.05≤t≤0.5, 0.70≤x3≤0.95, 0.05≤y3≤0.30, x3+y3+z3=1.0 and 0≤β≤0.5, M is at least one element selected from Co, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, Fe and W.)

[0129] Figure 3 This is a flowchart showing an example of a method for manufacturing a positive electrode active material according to the present embodiment. The method for manufacturing a positive electrode active material includes the following steps: mixing a nickel manganese composite hydroxide 10 (composite hydroxide 10) with a lithium compound to form a lithium mixture (step S3); and calcining the lithium mixture at a temperature of 800° C. or higher and 950° C. or lower in an oxidizing atmosphere to obtain a lithium nickel manganese composite oxide (step S4). Each step is described below.

[0130] (Mixing process)

[0131] First, the composite hydroxide 10 is mixed with a lithium compound to form a lithium mixture (step S3). As the lithium compound, known lithium compounds can be used without particular limitation, for example, from the viewpoint of easy availability, preferably lithium hydroxide, lithium nitrate, lithium carbonate, or a mixture thereof. Among them, as the lithium compound, lithium hydroxide or lithium carbonate is more preferred from the viewpoint of ease of operation and stability of quality.

[0132] It should be noted that, before the mixing step, the composite hydroxide 10 may be subjected to oxidative roasting, and at least a portion of the composite hydroxide 10, or all of it, may be made into the form of a nickel-manganese composite oxide and then mixed. By making it into the form of a nickel-manganese composite oxide, the reaction with the lithium compound becomes easier. Oxidative roasting can be carried out by a known method, for example, heat treatment in an oxidizing atmosphere. The temperature of the heat treatment can be set to the temperature for conversion into the composite oxide, and can be set to above 350° C. and below 750° C. In addition, the time of the heat treatment is usually about 1 to 12 hours.

[0133] The composite hydroxide 10 and the lithium compound are mixed so that the ratio (Li / Me) of the number of atoms of lithium (Li) in the lithium mixture to the number of atoms of metals other than lithium, i.e., the sum of the number of atoms of nickel, manganese and the element (M) (Me) is 0.95 or more and 1.50 or less, preferably 0.95 or more and 1.20 or less. Li / Me does not change before and after calcination, so the Li / Me ratio mixed in the mixing step becomes the Li / Me ratio in the positive electrode active material, and therefore, the mixing is performed in such a way that the Li / Me in the lithium mixture becomes the same as the Li / Me in the desired positive electrode active material.

[0134] In addition, a general mixer can be used for mixing, and a vibration mixer, Loedige mixer, Julia mixer, V-type mixer, etc. can be used. It is sufficient to mix to such an extent that the external shape of the composite hydroxide 10 is not destroyed.

[0135] (Baking process)

[0136] Next, the lithium mixture is calcined to obtain a lithium nickel manganese composite oxide (step S4). In the manufacturing method of this embodiment, the composite hydroxide 10 having the manganese-rich layer 2 is mixed with a lithium compound and calcined at a relatively high temperature (e.g., above 800°C and below 950°C). The degree of sintering of the secondary particles of the composite hydroxide 10 during calcination is related to the Mn / Ni ratio. If the Mn / Ni ratio is low (i.e., the Ni content ratio is high), the sintering degree increases. On the contrary, if the Mn / Ni ratio is high (i.e., the Mn content ratio is high), the sintering degree decreases. Thus, in the case where the particle surface has a manganese-rich layer 2, sintering during calcination can be suppressed. Furthermore, the amount of dissolved lithium is related to the calcination temperature. If the calcination temperature is high, the amount of dissolved lithium decreases, and if the calcination temperature is low, the amount of dissolved lithium increases. Thus, the composite hydroxide having a manganese-rich layer 2 on the surface and the lithium compound are calcined at a high temperature, so that the sintering of the secondary particles can be suppressed and the amount of dissolved lithium can be reduced.

[0137] In addition, by calcining at a high temperature, the elements in the manganese-rich layer 2 can be diffused, and the composition of the positive electrode active material after calcination can be made uniform. In addition, the composition of the positive electrode active material after calcination can be a part of the composition that is non-uniform, which is derived from the manganese-rich layer 2. The reaction resistance of the positive electrode active material having a manganese-rich layer 2 on the surface will increase, but when the composition of the positive electrode active material after calcination is uniform, the reaction resistance of the resulting secondary battery can be suppressed to a low level.

[0138] The uniformity of the composition of the positive electrode active material after calcination can be confirmed, for example, by analyzing the composition of the central part and the surface part of the secondary particles by EDX analysis of the scanning transmission electron microscope (S-TEM) of the cross section of the secondary particles. In the positive electrode active material (lithium metal composite oxide), the surface part is the part corresponding to the manganese-rich layer 2 in the composite hydroxide 10, and the part closer to the inside than the surface part is the central part. The composition uniformity of the lithium metal composite oxide can be evaluated by the composition ratio (manganese concentration ratio) of the surface part relative to the central part obtained by EDX analysis.

[0139] The manganese concentration ratio (manganese concentration in the surface part / manganese concentration in the center part) is preferably in the range of 0.9 or more and 1.2 or less from the viewpoint of reducing the reaction resistance. From the viewpoint of confirming the uniformity of the composition, the manganese concentration ratio can be measured by analyzing the EDX analysis value from the surface of the secondary particle to 5% of the radius as the surface part and the part closer to the inside as the center part. In the measurement, it is preferred to analyze multiple parts so that the average composition of the center part and the surface part of the secondary particles can be obtained, and it is preferred to analyze each of 3 points or more and average them. In addition, it is preferred that the measurement is to arbitrarily select 20 secondary particles having a volume average particle size of 80% to 120% relative to the volume average particle size (Mv) calculated from the particle size distribution measured by the laser diffraction scattering method, obtain the EDX analysis value for each selected secondary particle, and perform the number average.

[0140] Calcination is carried out at a temperature of 800°C or more and 950°C or less in an oxidizing atmosphere. When the calcination temperature is lower than 800°C, the diffusion of lithium cannot be fully carried out, excess lithium remains, and the amount of dissolved lithium sometimes increases. In addition, when the calcination temperature is lower than 800°C, calcination cannot be fully carried out, the tap density is reduced, or the uniformity of the composition of nickel, manganese, etc. inside the particles cannot be fully obtained, and when used in batteries, sufficient characteristics cannot sometimes be obtained. On the other hand, if it exceeds 950°C, sintering of secondary particles occurs, the secondary particles are coarsened, and the specific surface area is reduced. Therefore, when the obtained positive electrode active material is used in a battery, the resistance of the positive electrode increases, resulting in a problem of reduced battery capacity. In addition, the calcination time is not particularly limited, and is about 1 hour or more and about 24 hours.

[0141] It should be noted that, from the viewpoint of making the reaction of the composite hydroxide 10 or the nickel-manganese composite oxide obtained by oxidizing the composite hydroxide 10 and the lithium compound proceed uniformly, the heating rate is preferably, for example, raised to the above-mentioned calcination temperature in a range of 1°C / min or more and 10°C / min or less. Furthermore, before calcination, the temperature is maintained at a temperature near the melting point of the lithium compound for about 1 to 10 hours, so that the reaction can proceed more uniformly.

[0142] In addition, in the particle size distribution measured by the laser diffraction scattering method, the value obtained by dividing the cumulative 50 volume % particle size (D50) of the calcined lithium composite oxide by the cumulative 50 volume % particle size (D50) of the composite hydroxide 10 before calcination (lithium composite oxide D50 after calcination / composite hydroxide D50 before calcination) is preferably less than 1.2. If the above range is exceeded, the specific surface area is reduced due to the coarsened secondary particles. Therefore, when the obtained positive electrode active material is used in a battery, the resistance of the positive electrode increases, resulting in a problem of reduced battery capacity. In addition, the lower limit of the calcined lithium composite oxide D50 / composite hydroxide D50 before calcination is not particularly limited, for example, it can be above 0.80, or it can be above 0.90.

[0143] 5. Non-aqueous electrolyte secondary battery

[0144] For an example of a non-aqueous electrolyte secondary battery (hereinafter, also referred to as a "secondary battery") of the present embodiment, each constituent element is described separately. The secondary battery of the present embodiment is a secondary battery having a positive electrode, and the positive electrode contains the above-mentioned positive electrode active material. The secondary battery may include, for example, a positive electrode, a negative electrode and a non-aqueous electrolyte, or may include a positive electrode, a negative electrode and a solid electrolyte. The secondary battery of the present embodiment may be composed of the same constituent elements as a general lithium-ion secondary battery. Below, as an example of a secondary battery of the present embodiment, a secondary battery using a non-aqueous electrolyte is described. It should be noted that the embodiments described below are merely examples, and the secondary battery is represented by the following embodiments, and can be implemented in various ways with various changes and improvements based on the common sense of those skilled in the art. In addition, the use of the secondary battery is not particularly limited.

[0145] (positive electrode)

[0146] The positive electrode of the secondary battery is prepared using the positive electrode active material. An example of a method for manufacturing the positive electrode is described below. First, the positive electrode active material (powdered), a conductive material and a binder (binder) are mixed, and activated carbon and a solvent for adjusting the viscosity are further added as needed, and the mixture is kneaded to prepare a positive electrode composite material paste.

[0147] The mixing ratio of each material in the positive electrode composite material becomes a factor that determines the performance of the lithium secondary battery, and therefore, can be adjusted according to the purpose. The mixing ratio of the material can be set to be the same as the positive electrode of the known lithium secondary battery, for example, when the total mass of the solid component of the positive electrode composite material excluding the solvent is set to 100 mass%, it can contain 60 to 95 mass% of the positive electrode active material, 1 to 20 mass% of the conductive material, and 1 to 20 mass% of the binder.

[0148] The obtained positive electrode composite material paste is applied to the surface of a collector such as aluminum foil and dried to disperse the solvent to produce a sheet-like positive electrode. As needed, in order to increase the electrode density, a roller press is sometimes used for pressurization. The sheet-like positive electrode thus obtained can be cut into appropriate sizes according to the target battery, etc., for the production of the battery. Among them, the production method of the positive electrode is not limited to the method exemplified above, and can be based on other methods.

[0149] As the conductive material, for example, carbon black materials such as graphite (natural graphite, artificial graphite, expanded graphite, etc.), acetylene black, and Ketjen black can be used.

[0150] As the binder (adhesive), since it plays the role of fixing the active material particles, for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose resin, and polyacrylic acid can be used.

[0151] As required, a solvent for dispersing the positive electrode active material, the conductive material and the activated carbon and dissolving the binder is added to the positive electrode composite material. As the solvent, specifically, an organic solvent such as N-methyl-2-pyrrolidone can be used. In addition, in order to increase the electric double layer capacity, activated carbon can be added to the positive electrode composite material.

[0152] (negative electrode)

[0153] The negative electrode can use metallic lithium, lithium alloy, etc. In addition, the negative electrode can use the following formed material: a binder is mixed in the negative electrode active material capable of absorbing and deintercalating lithium ions, a suitable solvent is added to make a paste-like negative electrode composite material, the obtained negative electrode composite material is applied to the surface of a metal foil collector such as copper and dried, and the material formed by compression is formed as needed to increase the electrode density.

[0154] As the negative electrode active material, for example, a calcined body of an organic compound such as natural graphite, artificial graphite, and phenolic resin, and a powder of a carbon material such as coke can be used. In the above case, as the negative electrode binder, a fluorine-containing resin such as PVDF can be used in the same manner as the positive electrode, and as a solvent for dispersing these active materials and the binder, an organic solvent such as N-methyl-2-pyrrolidone can be used.

[0155] (Separator)

[0156] The positive electrode and the negative electrode are arranged so as to sandwich a separator. The separator is used to separate the positive electrode and the negative electrode and to retain the electrolyte, and a thin film having a large number of micropores such as polyethylene or polypropylene can be used.

[0157] (Non-aqueous electrolyte)

[0158] The non-aqueous electrolyte is a substance in which a lithium salt serving as a supporting salt is dissolved in an organic solvent. As the organic solvent, one selected from the following substances may be used alone or in combination: cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and trifluoropropylene carbonate; chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and dipropyl carbonate; ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, and dimethoxyethane; sulfur compounds such as ethyl methyl sulfone and butane sultone; phosphorus compounds such as triethyl phosphate and trioctyl phosphate, etc.

[0159] As supporting salts, LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, and complex salts thereof can be used. Furthermore, the non-aqueous electrolyte solution can contain a radical scavenger, a surfactant, a flame retardant, and the like.

[0160] (Battery shape and structure)

[0161] The nonaqueous electrolyte secondary battery of the present invention, which is composed of the positive electrode, negative electrode, separator and nonaqueous electrolyte as described above, can be made into various shapes such as cylindrical and stacked. In any shape, the nonaqueous electrolyte secondary battery is completed as follows: the positive electrode and the negative electrode are stacked with the separator to form an electrode body, the nonaqueous electrolyte is impregnated into the obtained electrode body, and the positive electrode collector is connected to the positive terminal connected to the outside and the negative electrode collector is connected to the negative terminal connected to the outside with a collector lead, and the battery case is sealed to complete it.

[0162] Example

[0163] Hereinafter, specific embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0164] (Example 1)

[0165] [Production of Composite Hydroxide]

[0166] (First Crystallization Step)

[0167] A prescribed amount of pure water was placed in a reaction tank (volume 60L), and the temperature (liquid temperature) in the reaction tank was set to 49°C while stirring, and nitrogen gas was circulated in the reaction tank to form a non-oxidizing atmosphere. The oxygen concentration in the space of the reaction tank at this time was 2.0%. The following were added simultaneously and continuously to the reaction tank: a 2.0 mol / L mixed aqueous solution in which nickel sulfate, cobalt sulfate, and manganese sulfate were dissolved so that the molar ratio of nickel: cobalt: manganese in the reaction tank was 80:10:10; a 25% by mass sodium hydroxide aqueous solution as an alkaline solution; and a 25% by mass ammonia water as a complexing agent, and a neutralization crystallization reaction was performed. At this time, the pH value of the reaction solution in the tank was adjusted to 12.3 based on a liquid temperature of 25°C. The ammonium ion concentration in the reaction tank was in the range of 12 to 15 g / L. The total flow rate of the mixed solution, the sodium hydroxide aqueous solution, and the ammonia water was controlled so that the residence time of the metal salt contained in the mixed aqueous solution was 8 hours. After the neutralization and crystallization reaction in the reaction tank becomes stable, the slurry containing the nickel-cobalt-manganese composite hydroxide is recovered from the overflow port.

[0168] (Second Crystallization Step)

[0169] The recovered slurry 30L was moved to another reaction tank (volume 60L), and the temperature (liquid temperature) in the reaction tank was set to 49°C while stirring, so that nitrogen gas was circulated in the reaction tank to form a non-oxidizing atmosphere. The oxygen concentration in the space of the reaction tank at this time was 2.0%. A 2.0 mol / L mixed aqueous solution 15L of nickel sulfate, cobalt sulfate and manganese sulfate was dissolved in the reaction tank at 0.10L / min so that the molar ratio of nickel: cobalt: manganese in the reaction tank became 50:10:40. At the same time, 25% by mass ammonia water and 25% by mass sodium hydroxide aqueous solution were gradually added to the reaction solution in the reaction tank at a constant rate. While keeping the ammonia concentration in the reaction solution in the range of 12 to 15g / L, the pH value was controlled to be 11.2 based on the liquid temperature of 25°C, and crystallization was performed for 2 hours and 30 minutes, and the product was filtered to obtain a filter cake of nickel-manganese composite hydroxide. After filtration, 1 L of pure water was supplied to the nickel-manganese composite hydroxide cake in the filter to remove impurities. The washed nickel-manganese composite hydroxide cake was then air-dried at 120° C. to obtain nickel-manganese composite hydroxide.

[0170] The surface and cross-sectional structure of the obtained nickel-manganese composite hydroxide were observed using a scanning electron microscope (SEM). Figure 4 A and B show the surface of the obtained nickel-manganese composite hydroxide ( Figure 4 A) and cross-sectional structure ( Figure 4B). The results of surface observation confirmed that secondary particles with high sphericity can be obtained. Next, the cross-section of the secondary particles was observed by SEM at a magnification of 1000 times, and 20 secondary particles with a volume average particle size of 80% to 120% relative to the volume average particle size (Mv) calculated from the particle size distribution measured by the laser diffraction scattering method were arbitrarily selected. For each selected secondary particle, the ratio of the thickness of the manganese-enriched layer to the radius (%) was calculated, and the measured values ​​of each secondary particle were averaged to calculate the ratio of the thickness of the manganese-enriched layer of the nickel-manganese composite hydroxide. It was confirmed that the thickness of the periphery (manganese-enriched layer) was 7.8% of the secondary particle size.

[0171] The particle size distribution of the obtained nickel-manganese composite hydroxide was measured using a laser diffraction scattering particle size distribution measuring device. As a result, the volume average particle size MV was 10.8 μm and [(D90-D10) / average particle size] was 0.87.

[0172] The tap density of the obtained nickel-manganese composite hydroxide was calculated as follows: the tap density was 2.00 g / cm2 after 500 taps using a tapping device (KYT3000 manufactured by SEISHINENTERPRISE Co., Ltd.). 3 .

[0173] The obtained nickel-manganese composite hydroxide was dissolved with an inorganic acid and then chemically analyzed by ICP emission spectrometry. The composition was Ni 0.70 Co 0.10 Mn 0.20 The properties of the obtained nickel-manganese composite hydroxide are shown in Table 1.

[0174] [Preparation of positive electrode active material]

[0175] The nickel-manganese composite hydroxide was placed in a calcination container made of magnesium oxide, heated to 500° C. for 2 hours in an air atmosphere with a flow rate of 12 L / min in a closed electric furnace, and then cooled to room temperature to obtain a nickel-manganese composite oxide.

[0176] The nickel-manganese composite oxide and lithium carbonate were weighed so that Li / Me became 1.03, and then mixed thoroughly with a vibration stirrer (TURBULA Type T2C manufactured by WAB (Willy A. Bachofen AG) at a strength sufficient to maintain the shape of the precursor to obtain a lithium mixture (mixing step).

[0177] The lithium mixture is embedded in a calcination container made of magnesium oxide, and the temperature is raised to 860°C at a heating rate of 3.00°C / min in an oxygen atmosphere with a flow rate of 12 L / min in a closed electric furnace, maintained for 10 hours, and the furnace is cooled to room temperature to obtain a lithium metal composite oxide (calcination process).

[0178] The surface structure of the obtained positive electrode active material was observed by a scanning electron microscope, and the result confirmed that particles with good sphericity could be obtained, similar to the nickel-manganese composite hydroxide. The circularity of the obtained positive electrode active material was calculated by a flow particle image analyzer (FPIA-3000 manufactured by Sysmex), and the circularity was 0.961.

[0179] The half-value width of the (003) plane of the obtained positive electrode active material was measured by an X-ray diffraction device (PANalytical X'Pert PRO). From the obtained half-value width of the (003) plane, the crystallite diameter of the (003) plane was calculated by Scherrer's calculation formula. The result was:

[0180] 20 g of the obtained positive electrode active material was taken, put into 100 cc of pure water at 25°C, immersed and stirred for 30 minutes. The supernatant after standing for 10 minutes was titrated with HCl aqueous solution and the dissolved lithium was calculated to be 0.12 wt%.

[0181] The particle size distribution of the obtained positive electrode active material was measured in the same manner as the above-mentioned nickel manganese composite hydroxide. It was confirmed that the average particle size was 10.5 μm, and [(D90-D10) / average particle size] was 0.83. In addition, the value obtained by dividing the cumulative 50 volume % particle size (D50) of the above-mentioned calcined product by the cumulative 50 volume % particle size (D50) of the above-mentioned nickel composite hydroxide was 0.97.

[0182] The specific surface area of ​​the obtained positive electrode active material was measured by the BET method based on nitrogen adsorption. The result showed that the specific surface area was 0.35 m 2 / g.

[0183] The tap density of the obtained positive electrode active material was measured in the same manner as the above nickel-manganese composite hydroxide. As a result, the tap density was 2.48 g / cm 3 .

[0184] The obtained positive electrode active material was dissolved with an inorganic acid and then chemically analyzed by ICP emission spectroscopy. The composition was Li 1.03 Ni 0.70 Co 0.10 Mn 0.20 O2, it was confirmed that particles of the target composition could be obtained.

[0185] The cross section of the secondary particles of the obtained positive electrode active material (lithium metal composite oxide) was subjected to EDX analysis using a scanning transmission electron microscope (S-TEM). 20 secondary particles having a volume average particle size of 80% to 120% relative to the volume average particle size (Mv) calculated from the particle size distribution measured by the laser diffraction scattering method were randomly selected. The area from the surface of each selected secondary particle to 5% of the radius was taken as the surface part. For the surface part and the center part closer to the inside than the surface part, any 5 points of each were analyzed and averaged to find the composition ratio (manganese concentration ratio) of the surface part relative to the center part in each secondary particle. The manganese concentration ratio of each secondary particle was averaged by number to find the manganese concentration ratio of the positive electrode active material. The characteristics of the obtained positive electrode active material are shown in Table 2.

[0186] [Battery production]

[0187] 52.5 mg of the obtained positive electrode active material, 15 mg of acetylene black, and 7.5 mg of polytetrafluoroethylene resin (PTFE) were mixed and press-formed at a pressure of 100 MPa into a diameter of 11 mm and a thickness of 100 μm to prepare a Figure 5 The positive electrode (evaluation electrode) PE shown. After the prepared positive electrode PE was dried in a vacuum dryer at 120°C for 12 hours, the positive electrode PE was used to make a 2032-type coin battery CBA in a glove box with an Ar atmosphere whose dew point was managed at -80°C. The negative electrode NE used lithium (Li) metal with a diameter of 17 mm and a thickness of 1 mm, and the electrolyte used was an equal mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1M LiClO4 as the supporting electrolyte (produced by Toyama Pharmaceutical Industry Co., Ltd.). The separator SE used was a polyethylene porous membrane with a film thickness of 25μm. In addition, the coin battery has a gasket GA and a corrugated gasket WW, and is assembled into a coin-shaped battery by the positive electrode can PC and the negative electrode can NC.

[0188] After making the coin-shaped battery, place it for about 24 hours. After the open circuit voltage (OCV) stabilizes, set the current density at the positive electrode to 0.1 mA / cm 2 , charge until the cut-off voltage is 4.3V, rest for 1 hour, and then discharge until the cut-off voltage is 3.0V, and the capacity at this time is taken as the initial discharge capacity. The discharge capacity uses a multi-channel voltage / current generator (made by ADVANTEST CORPORATION, R6741A). In addition, the discharge voltage is calculated from the results of the charge and discharge measurements, and the volume energy density is calculated from this value, the tap density, and the initial discharge capacity according to the formula of volume energy density (Wh / L) = average discharge voltage (V) × discharge capacity (A / kg) × tap density (kg / L). The measurement results of the initial charge and discharge capacity and volume energy density of the obtained active material are shown in Table 2.

[0189] (Example 2)

[0190] The nickel-manganese composite hydroxide (precursor) and the positive electrode active material were prepared in the same manner as in Example 1 except that the molar ratio of nickel:cobalt:manganese in the second mixed aqueous solution supplied in the crystallization coating step (second crystallization step) was adjusted to 40:10:50 and the supply amount of the second mixed aqueous solution was 10 L. The properties of the obtained nickel-manganese composite hydroxide are shown in Table 1. In addition, the properties of the obtained positive electrode active material and the electrochemical property evaluation results are shown in Table 2.

[0191] (Example 3)

[0192] A nickel manganese composite hydroxide and a positive electrode active material were prepared in the same manner as in Example 1 except that the calcination temperature in the calcination step was 880° C. The properties of the obtained nickel manganese composite hydroxide are shown in Table 1. Table 2 also shows the properties of the obtained positive electrode active material and the results of electrochemical property evaluation.

[0193] (Comparative Example 1)

[0194] The molar ratio of nickel:cobalt:manganese in the mixed aqueous solution supplied in the continuous crystallization step was adjusted to 70:10:20, the crystallization coating step was omitted, and the slurry whose pH was adjusted to 12.0 based on a liquid temperature of 25° C. was filtered and washed to obtain a composite hydroxide. Except for this, a nickel-manganese composite hydroxide and a positive electrode active material were prepared in the same manner as in Example 1. The properties of the obtained nickel-manganese composite hydroxide are shown in Table 1, and the surface and cross-sectional structures are shown in Figure 4 C and Figure 4 In addition, the characteristics of the obtained positive electrode active material and the results of electrochemical characteristic evaluation are shown in Table 2.

[0195] (Comparative Example 2)

[0196] A nickel manganese composite hydroxide and a positive electrode active material were prepared in the same manner as in Example 1 except that the calcination temperature in the calcination step was 970° C. The properties of the obtained nickel manganese composite hydroxide are shown in Table 1. Table 2 also shows the properties of the obtained positive electrode active material and the results of electrochemical property evaluation.

[0197] (Comparative Example 3)

[0198] A nickel manganese composite hydroxide and a positive electrode active material were prepared in the same manner as in Example 1 except that the calcination temperature in the calcination step was 760° C. The properties of the obtained nickel manganese composite hydroxide are shown in Table 1. Table 2 also shows the properties of the obtained positive electrode active material and the results of electrochemical property evaluation.

[0199] [Table 1]

[0200]

[0201] [Table 2]

[0202]

[0203] (Evaluation results)

[0204] In the nickel-manganese composite hydroxide of the embodiment, a manganese-enriched layer with a moderate thickness is provided at the periphery, and even if the calcination temperature is set to a relatively high temperature, it is not easy to cause sintering of the secondary particles during calcination, and the positive electrode active material after calcination can take into account both high capacity and reduced amount of dissolved lithium at a high level. In addition, the positive electrode active material of the embodiment has a high circularity, less sintering of the secondary particles, excellent particle filling, and can obtain a high volume energy density.

[0205] For Comparative Example 1, the calcination temperature is high, so the dissolution of Li can be reduced to the same level as in the example. However, the nickel-manganese composite hydroxide does not have a manganese-enriched layer, so it is easy to cause sintering of the secondary particles compared to the nickel-manganese composite hydroxide of the example during calcination, and the specific surface area of ​​the positive electrode active material after calcination is low, resulting in particles with low tap density. Therefore, compared with the example, the volume energy density becomes lower.

[0206] For the nickel-manganese composite hydroxide of Comparative Example 2, the roasting temperature is too high, so compared with the nickel-manganese composite hydroxide of the embodiment, the secondary particles are sintered with each other during roasting, and the specific surface area of ​​the positive electrode active material after roasting is low, becoming particles with low tap density. Therefore, compared with the embodiment, the volume energy density is lowered. In addition, the roasting temperature is too high, so the atomic arrangement in the crystal is disordered, and therefore, compared with the embodiment, the initial charge and discharge capacity is lowered.

[0207] In Comparative Example 3, the calcination temperature was low and the reaction with the Li compound during calcination did not proceed sufficiently. Therefore, the amount of lithium dissolved from the positive electrode active material after calcination was large and the charge-discharge capacity was low compared to the examples.

[0208] As described above, a manganese-enriched layer of a specific thickness is provided on the surface of the nickel-manganese composite hydroxide, and the calcination temperature is adjusted to an optimal value, thereby suppressing sintering during calcination, dissolving less lithium, and obtaining a positive electrode active material that can take into account both high capacity and high energy density. In addition, when the positive electrode active material of this embodiment is used to make a paste, gelation can be suppressed.

[0209] It should be noted that the protection scope of the present invention is not limited to the methods described in the above-mentioned embodiments, etc. Sometimes one or more of the features described in the above-mentioned embodiments, etc. are omitted. In addition, the features described in the above-mentioned embodiments, etc. can be appropriately combined. In addition, within the scope permitted by law, the disclosure of all documents cited in the special application 2016-213413 of Japanese patent application and this specification are introduced as part of the records of this article.

[0210] Description of Reference Numerals

[0211] 10…Nickel-manganese composite hydroxide

[0212] 1…Secondary particles

[0213] 2…Manganese-rich layer

[0214] 3…Center

[0215] r…radius of the secondary particle

[0216] t…thickness of the manganese-rich layer

[0217] PE…Positive electrode (evaluation electrode)

[0218] NE…Negative electrode

[0219] SE…Separator

[0220] GA...Gasket

[0221] WW…Wave Washer

[0222] PC…Positive electrode tank

[0223] NC…Cathode tank

Claims

1. A positive electrode active material for a non-aqueous electrolyte secondary battery, which is formed by a lithium nickel manganese composite oxide having a hexagonal layered structure, wherein the lithium nickel manganese composite oxide comprises secondary particles formed by a plurality of primary particles agglomerated with each other, and is represented by the general formula (3): Li 1+t Ni x3 Mn y3 M z3 O 2+β It means that in the formula (3), -0.05≤t≤0.5, 0.70≤x3≤0.95, 0.05≤y3≤0.30, x3+y3+z3=1.0 and 0≤β≤0.5 are satisfied, and M is at least one element selected from Co, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, Fe and W, The positive electrode active material for a non-aqueous electrolyte secondary battery has a secondary particle circularity of 0.95 or more calculated by image analysis. The (003) crystallite diameter measured by X-ray diffraction is 160 nm or more and 200 nm or less, When immersed in water, the amount of lithium eluted into water is 0.2 mass % or less based on the entire positive electrode active material.

2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein In the particle size distribution measured by a laser diffraction scattering method, the volume average particle size (Mv) is greater than 4 μm and less than 20 μm, and the particle size fluctuation index [(D90-D10) / Mv] calculated from the cumulative 90 volume% particle size (D90), the cumulative 10 volume% particle size (D10) and the volume average particle size (Mv) is greater than 0.

60.

3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or claim 2, wherein the specific surface area is 0.20 m 2 / g or more and 0.70m 2 / g or less.

4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or claim 2, wherein the tap density is 2.2 g / cm 3 Above and 3.6g / cm 3 the following. 5 . A nonaqueous electrolyte secondary battery comprising a positive electrode, wherein the positive electrode comprises the positive electrode active material according to claim 1 .

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary cell

    JP2011076797A

  • Li-ni composite oxide particle powder for nonaqueous electrolyte secondary battery, method of manufacturing the same, and nonaqueous electrolyte secondary battery

    JP2011113885A

  • Positive electrode active material for nonaqueous electrolyte secondary batteries and method for manufacturing the same

    JP2015056368A

  • Semiconductor device

    JP2016213413A

  • Nickel composite hydroxide, positive electrode active material for non-aqueous electrolyte secondary cell, non-aqueous electrolyte secondary cell, and methods for producing these

    CN104379509A